Scope Of Islamic Educational Philosophy - Van Adiputra, Rich; Husniyah, Nur Iftitahul (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The world of Islamic education in Indonesia in particular, and the Islamic world in general are still faced with various problems, starting from the question of the formulation of educational goals that are not in line with the demands of society, to the problems of teachers, methods, curriculum and so on. Efforts to overcome this problem are still being carried out in various ways, such as upgrading teachers, training for education management staff and so on, but along with developments in life, educational problems continue to emerge. For this reason, Islamic Education Philosophy is present as one of the offered solutions. As a philosophical study, Islamic Education Philosophy seeks to use philosophical services, namely thinking in depth, systematically, radically and universally to solve educational problems, such as problems of students, teachers, curriculum, methods and the environment by using the Qur'an and al-Hadith as the basic reference. The aims of this research are (1) to know the meaning of Islamic Education Philosophy, and (2) to know the urgency of the scope of Islamic Education Philosophy. Based on the results of the analysis carried out, the results of this study are: (1) Philosophy of Islamic Education can be interpreted as a study of traditional, critical, and radical philosophical views and schools of thought in Islam towards educational issues. He answered the influence of education on the development and growth of Muslim humans and Muslims in general. It is also a means of solving various problems in Muslim education, (2) the scope of the philosophy of Islamic education is issues related to educational activities, such as curriculum, methods, and the environment. Philosophically, educators or teachers as teachers must understand in depth the curriculum, methods, and learning environment so that they can maximize the learning process.